The Effect Of Promotion And Brand Awareness On Customer Satisfaction At PLN ULP Polewali - Pandi Putra; Bakhtiar Tijjang; Safrida; Sundari (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
The objectives of this study are (1) To determine the partial influence of Promotion and Brand Awareness on Customer Satisfaction at PLN ULP Polewali (2) To determine the simultaneous influence of Promotion and Brand Awareness on Customer Satisfaction at PLN ULP Polewali. The data collection methods used in this study were observation, interviews, questionnaires, and documentation. The sample was determined using the Slovin formula, resulting in 396 respondents. The analysis method used multiple linear regression with the help of SPSS Version 25. The results of this study indicate that (1) Partially, Promotion has a significant effect on Customer Satisfaction at PLN ULP Polewali. Partially, Brand Awareness has a significant effect on Customer Satisfaction at PLN ULP Polewali. (2) Simultaneously, Promotion and Brand Awareness have a significant effect on Customer Satisfaction at PLN ULP Polewali. The results of the determination coefficient of 0.955 indicate that the Tangible independent variable influences the dependent variable, namely 95.5%, therefore for researchers who will research with the same theme, it is recommended to add other variables that are not yet included in this study so that the research results can be better and prove the hypothesis. This will possibly provide comparative results of the influence of previous research.